Worker betas: Five facts about systematic earnings risk - Fatih Guvenen; Sam Schulhofer-Wohl; Jae Song; Motohiro Yogo (Federal Reserve Bank of Chicago, 2017)
The magnitude of and heterogeneity in systematic earnings risk has important implications for various theories in macro, labor, and financial economics. Using administrative data, we document how the aggregate risk exposure of individual earnings to GDP and stock returns varies across gender, age, the worker's earnings level, and industry. Aggregate risk exposure is U-shaped with respect to the earnings level. In the middle of the earnings distribution, males, younger workers, and those in construction and durable manufacturing are more exposed to aggregate risk. At the top of the earnings distribution, older workers and those in finance are more exposed to aggregate risk. Workers in larger employers are less exposed to aggregate risk, but they are more exposed to a common factor in employer-level earnings, especially at the top of the earnings distribution. Within an employer, higher-paid workers have higher exposure to the employer-level risk than lower-paid workers.
Keywords: D31; G11; 330